Irreversible atrophy in memory brain regions over 7 years is predicted by glycemic control in type 2 diabetes without mild cognitive impairment - Canário, Nádia; Crisóstomo, Joana; Duarte, João Valente; Moreno, Carolina; Quental, Hugo; Gomes, Leonor; Oliveira, Francisco; Castelo-Branco, Miguel (Frontiers in Aging Neuroscience, 2024)
Memory-related impairments in type 2 diabetes may be mediated by insulin resistance and hyperglycemia. Previous cross-sectional studies have controversially suggested a relationship between metabolic control and a decrease in hippocampal volumes, but only longitudinal studies can test this hypothesis directly. We performed a longitudinal morphometric study to provide a direct test of a possible role of higher levels of glycated hemoglobin with long term brain structural integrity in key regions of the memory systemhippocampus, parahippocampal gyrus and fusiform gyrus. Grey matter volume was measured at two different timesbaseline and after ~ 7 years. We found an association between higher initial levels of HbA1C and grey matter volume loss in all three core memory regions, even in the absence of mild cognitive impairment.Importantly, these neural effects persisted in spite of the fact that patients had significantly improved their glycemic control. This suggests that early high levels of HbA1c might be irreversibly associated with subsequent long-term atrophy in the medial temporal cortex and that early intensive management is critical.